Implementation of English "Online and Offline" Hybrid Teaching Recommendation Platform Based on Reinforcement Learning. (30th September 2021) - Dong, Danling; Wu, Libo
Abstract : At present, there is a serious disconnect between online teaching and offline teaching in English MOOC large-scale hybrid teaching recommendation platform, which is mainly due to the problems of cold start and matrix sparsity in the recommendation algorithm, and it is difficult to fully tap the user's interest characteristics because it only considers the user's rating but neglects the user's personalized evaluation. In order to solve the above problems, this paper proposes to use reinforcement learning thought and user evaluation factors to realize the online and offline hybrid English teaching recommendation platform. First, the idea of value function estimation in reinforcement learning is introduced, and the difference between user state value functions is used to replace the previous similarity calculation method, thus alleviating the matrix sparsity problem. The learning rate is used to control the convergence speed of the weight vector in the user state value function to alleviate the cold start problem. Second, by adding the learning of the user evaluation vector to the value function estimation of the state value function, the state value function of the user can be estimated approximately and the discrimination degree of the target user can be reflected. Experimental results show that the proposed recommendation algorithm can effectively alleviate the cold start and matrix sparsity problems existing in the current collaborative filtering recommendation algorithm and can dig deep into the characteristics of users' interests and further improve the accuracy of scoring prediction.